Characterization of wheat yellow rust and stem rust virulence in Southern Spain - Rodríguez-Vázquez, Jaime Nolasco; Ammar, Karim; Solís, Ignacio; Martínez-Moreno, Fernando (MDPI, 2023)
Effective mitigation of the current threat from yellow rust and the potential threat from stem rust to wheat production in the south of Spain requires the characterization of the lineages/races currently present in the region. Results from this study clearly indicated that the main yellow rust lineages currently present in the south of Spain are PstS10, PstS13, and PstS14, to which several widely grown commercial cultivars are resistant. Even though stem rust is not yet present during the regular cropping season, the main lineages/races Clade IV-B and Clade IV-F, were identified, much like in most of Europe and parts of North Africa. The evaluation of differential series and special breeding lines with known genes under local conditions has indicated the availability of several genetic options that could be used in breeding/selection programs to provide effective levels of resistance to either disease in the future. However, in undertaking these efforts, it is important to consider not only the lineages currently present locally but also resistance options effective against lineages/races that are rapidly developing elsewhere and could very likely reach the south of Spain in the near future.